OUTCOMES COMPARISON OF DIRECT STENTING VERSUS PRE-DILATION IN PERCUTANEOUS CORONARY INTERVENTION (Journal of Medical & Health Sciences Review, 2025)
Introduction: Percutaneous coronary intervention (PCI) has become an intervention of choice in the treatment of coronary artery disease. The traditional procedures are direct stenting and pre-dilation, and the outcomes of the two approaches remain an open debate.Objective: To compare the outcome of direct stenting and pre-dilation during the procedure of PCI and focus on the success of the procedure, comorbidity rates, and long-term clinical outcomes.Materials and Methods: The study was carried out as a prospective study conducted at Department of Cardiology, Ch Pervaiz Elahi Institute of Cardiology, Multan in the duration from January, 2025 to June, 2025. This study involved 100 patients who were undergoing PCI. The patients were randomly divided into direct stenting and pre-dilation groups. Measures of procedure success, complications, procedural time, and contrast volume were obtained. A six-month follow-up was done to determine the long-term outcomes.Results: Direct stenting had much lower complication rates, procedural time, and contrast volume than both groups, which had high procedural success rates. Restenosis and revascularization were comparable between groups after a prolonged period of time.Conclusion: Direct stenting is a safer and more effective substitute for pre-dilation, especially when a less complex lesion is involved. Nonetheless, more complicated lesions still require pre-dilation.